Sense and sensibility: Testing an attention‐based view of organizational responses to social issues. (2nd August 2017) - Ferreira, Luciana Carvalho de Mesquita
Abstract : According to attention‐based theories, to explain organizational attention is to explain organizational behavior. In our study, we test the model of situated attention and firm behavior by examining the effects of attention structures and allocation of attention on organizational outcomes. We hypothesize a positive relationship between attention structures and the allocation of organizational attention that, in turn, has an effect on financial performance. Using a unique data set composed of indicators of social responsibility published by 338 Brazilian organizations between 2001 and 2007, we find support for our hypotheses. Our findings suggest that organizational attention to social issues fully mediates the relationship between attention structures and financial performance.